Job Demands–Resources and Burnout in Public Sector: A Systematic Literature Review - Fitri Angraini; Nimmi Zulbainarni; Anggraini Sukmawati (LPPM Institut Bisnis dan Informatika Kesatuan, 2026)
This study is motivated by the high prevalence of burnout among public sector employees, which has significant implications for individual well-being and organizational effectiveness. This study aims to map empirical evidence on burnout within the Job Demands–Resources (JD-R) framework, specifically by identifying the dimensions of job demands and job resources and examining their relationships with burnout in the public sector. This research employed a Systematic Literature Review (SLR) following PRISMA guidelines, using the Scopus database for studies published between 2001 and 2025, resulting in 14 selected articles. The findings indicate that quantitative demands are the most dominant predictors of burnout, followed by organizational structure and work arrangement demands, while mental and emotional demands remain relatively underexplored. On the other hand, interpersonal and social resources, such as supervisor and coworker support as well as a positive organizational climate, emerge as the most important protective factors against burnout. Burnout occurs when high job demands are not adequately balanced by sufficient job resources. The study concludes that maintaining a balance between job demands and job resources is essential for preventing burnout. Practically, public sector organizations should manage workload, clarify role expectations, and strengthen social support and organizational climate to enhance employee well-being.